1999
DOI: 10.1073/pnas.96.23.13214
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Purkinje fiber differentiation by coronary arterialization

Abstract: A synchronized heart beat is controlled by pacemaking impulses conducted through Purkinje fibers. In chicks, these impulse-conducting cells are recruited during embryogenesis from myocytes in direct association with developing coronary arteries. In culture, the vascular cytokine endothelin converts embryonic myocytes to Purkinje cells, implying that selection of conduction phenotype may be mediated by an instructive cue from arteries. To investigate this hypothesis, coronary arterial development in the chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 28 publications
1
52
2
1
Order By: Relevance
“…Although apparently elevated expression might represent local maintenance of a higher steady-state level of Nkx-2.5 mRNA from earlier stages of development, this cannot be the case for these newly recruited cells, especially the periarterial Purkinje fibres. These arise in the chick embryo from a previously lowexpressing population following in-growth of coronary arterial progenitors (Gittenberger-de Groot et al, 1998;Hyer et al, 1999). We propose our results support the hypothesis of a role for Nkx-2.5 in the regulation of selection and/or maintenance of specialized fate within the cardiomyogenic lineage.…”
Section: Discussionsupporting
confidence: 79%
“…Although apparently elevated expression might represent local maintenance of a higher steady-state level of Nkx-2.5 mRNA from earlier stages of development, this cannot be the case for these newly recruited cells, especially the periarterial Purkinje fibres. These arise in the chick embryo from a previously lowexpressing population following in-growth of coronary arterial progenitors (Gittenberger-de Groot et al, 1998;Hyer et al, 1999). We propose our results support the hypothesis of a role for Nkx-2.5 in the regulation of selection and/or maintenance of specialized fate within the cardiomyogenic lineage.…”
Section: Discussionsupporting
confidence: 79%
“…The recruitment of cardiomyocytes into the Purkinje fiber system has been demonstrated to be related to hemodynamic influences derived from the coronary vasculature and endocardial lining of the ventricular lumen Hyer et al, 1999), with mature ET-1 and the ECE1 metalloprotease as key inductive factors (Takebayashi-Suzuki et al, 2000;Reckova et al, 2003;Hall et al, 2004). Earlier work demonstrated dramatic effects on the development of cardiac architecture and coronary vasculature when epicardial differentiation was disturbed (Gittenberger-de Groot et al, 2000;Tevosian et al, 2000;Lie-Venema et al, 2003;Eralp et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral tagging experiments showed that the Purkinje fibers of the peripheral conduction system differentiate from cardiomyocytes, in close spatiotemporal relation to the developing coronary vasculature Hyer et al, 1999), whereas the subendocardial Purkinje fibers develop in the proximity of endocardial cells. These unique differentiation sites suggested an inductive role both for periarterial and subendocardial EPDCs and for a paracrine signal from the endocardium and arterial beds in the recruitment of cardiomyocytes into the Purkinje fiber network (Gittenberger-de Groot et al, 2003b;Gourdie et al, 2003).…”
mentioning
confidence: 99%
“…At the cellular level, efficient impulse propagation through this network is dependent upon the interplay between cell morphology, membrane excitability, and electrical coupling of adjacent cells via gap junctions, the latter of which is the major determinant for rapid and directional conduction (3). Although regulation of early VCS specification and morphogenesis is becoming well understood (4)(5)(6)(7)(8)(9), less is known about how cells of the VCS gain their specialized conduction properties as they mature.…”
mentioning
confidence: 99%